DESEMPENHO DO RENDIMENTO INDUSTRIAL E DE GRÃOS PARA A ESTIMATIVA DE ASSOCIAÇÃO DOS CARACTERES EM AVEIA BRANCA - Zambonato, Felipe; Valentini, Ana P. F.; Martins, João A. K.; Gaviraghi, Fernando; Wagner, Juliano F.; Cadore, Pablo R.; Krüger, Cleusa A. M. B.; Soares, Rômulo D.; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo